(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. There are few studies about the variables of the duration of power- endurance workloads and their total and residual effects. Research aim was to evaluate the changes in the functional state indices of muscular and cardiovascular systems while two training micro-cycles were designed to develop power-endurance abilities, and the third one was appointed for active rest. Research methods: Seven sprint athletes performed two micro-cycles of concentrated power-endurance type loads and one micro-cycle was appointed for recovery. Three groups of indices were chosen: muscular power; cardiovascular indices and indices of recovery. 12-leads ECG was registered during the Ruffier test and 30 s vertical jumping tests. Research results. Under the influence of two training micro-cycles using concentrated power endurance workloads muscular power deteriorated and the recovery rate was individual. After two training micro-cycles the effect of total fatigue caused an increased biological efforts to perform the locomotion task and cardiovascular changes were more expressed than before training. Seven days was a too short period of time so that the changes in the indices caused by total effect of training would return to the baseline values again. Discussion and conclusions. Reduced abilities in the regulation of peripheral vascular tone after heavy training could be compensated by the changes in the cardiac function, i. e. by an increase in systolic blood pressure. Cardiovascular indices could be useful for describing changes in the functional state of athletes under the influence of training. Keywords: cardiovascular system, recovery, anaerobic load.